Numerical Study of Three Different Approaches to Simulate Nanofluids Flow and Heat Transfer in a Microtube - Salman B.H.; Mohammed H.A.; Kherbeet A.S.H. (John Wiley and Sons Inc., 2023)
Mixtures; Nanofluidics; Numerical models; Flow and heat transfer; Forced convective flows; Heat Transfer enhancement; Laminar and turbulent flow; Microtube; Nanofluids; Single-phase model; Two phase; Heat transfer